Bioactive Polysaccharides from Fermented Dendrobium officinale: Structural Insights and Their Role in Skin Barrier Repair - Wanshuai Wang; Anqi Zou; Qingtao Yu; Zhe Wang; Daotong Tan; Kaiye Yang; Chao Cai; Guangli Yu (Molecules)
Dendrobium, a prominent genus in the Orchidaceae family, has generated significant research attention due to its demonstrated biological potential, particularly its notable anti-inflammatory and antioxidant activities. In this study, two fractions of fermented Dendrobium officinale polysaccharides (FDOPs) were successfully isolated through a multi-stage purification strategy including gradient ethanol precipitation, gel column chromatography, and ion exchange chromatography with Lactobacillus reuteri CCFM863. Structural characterization revealed that both Dendrobium officinale polysaccharide fractions consisted of (1→4)-β-D-Manp, (1→4)-β-D-Glcp, and (1→4)-α-D-Glcp residues. The anti-inflammatory efficacy and keratinocyte-protective potential of FDOPs (FDOP-1A and FDOP-2A) were investigated by using lipopolysaccharide (LPS)-induced RAW264.7 and HaCaT cells models, which showed significant inhibitions on the inflammatory factors of monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α), nitric oxide (NO), and interleukin-1 beta (IL-1β); recovered levels of filaggrin (FLG), aquaporin 3 (AQP3), transient receptor potential vanilloid 4 (TRPV4), cathelicidin antimicrobial peptide (CAMP)/LL-37, and adiponectin (ADIPOQ); and the reduced protein expression of the TLR4/IκB-α/NF-κB/NLRP3 pathway. Notably, the FDOPs exhibited a remarkable reactive oxygen species (ROS) scavenging capacity, demonstrating superior antioxidant activity. Therefore, FDOPs show dual anti-inflammatory and antioxidant properties, making them suitable as active ingredients for modulating epidermal inflammation and promoting skin barrier repair.